Environmentally Benign Large-Scale Synthesis of a Precursor to Vortioxetine - Zisopoulou, Stavroula A.; Pafili, Anastasia E.; Gkizis, Petros; Andreou, Thanos; Koftis, Theoharis V.; Lithadioti, Alexandra; Neokosmidis, Efstratios; Gallos, John K. (Synthesis, 2020)
An eco-friendly, high-yielding, and transition-metal-free synthesis of 2-[(2,4-dimethylphenyl)thio]aniline precursor to vortioxetine is reported. Vortioxetine, a multi-modal acting drug with high affinity for a range of serotonergic targets, is used for the treatment of major depressive disorder (MDD). The synthesis – applicable in multi-gram scale – involves the reaction of bis(2,4-dimethyl)iodonium bromide with commercial 2-aminophenyl disulfide, whereas its reaction with 2-aminothiophenol afforded the same product but in low to moderate yields. This method works equally well in deep eutectic solvents (DESs), based on choline chloride (ChCl).
Keywords: iodonium salts; vortioxetine; major depressive disorder; green chemistry; deep eutectic solvents; hypervalent iodine